2005
DOI: 10.1111/j.1751-0813.2005.tb13299.x
|View full text |Cite
|
Sign up to set email alerts
|

Udder development, lactation and ascites in a ewe with an ovarian granulosa cell tumour

Abstract: A 20-month-old sexually intact female mixed breed sheep was examined for lameness, unexpected udder development, lactation and anorexia. Tachycardia, tachypnoea, severe abdominal distension and vaginal prolapse were evident upon physical examination. A right hindlimb lameness was present at the walk. The udder was well-developed and milk, normal in appearance, was easily expressed from each teat. Ultrasonographic evaluation revealed a non-pregnant uterus, severe ascites and a large (12 cm diameter) abdominal m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 8 publications
0
10
1
1
Order By: Relevance
“…Discussion Progressive weight loss was the only clinical sign observed in our case of malignant granulosa cell tumour in a ewe, in contrast to previously described cases of these tumours e.g. in mares and a bitch where a variety of clinical signs were described, for example: lameness, udder development, lactation and anorexia (Gardner et al 2005), progressive weight loss, diarrhoea and depression (Patrick et al 2003), anorexia (Sabocanec et al 1996Patrick et al 2003), and lameness (Gift et al 1992). Production of hormones in the neoplastic ovary may result in behavioural abnormalities and alterations in the oestrus cycle (Stabenfeldt et al 1979).…”
Section: Immunohistochemistrycontrasting
confidence: 49%
See 2 more Smart Citations
“…Discussion Progressive weight loss was the only clinical sign observed in our case of malignant granulosa cell tumour in a ewe, in contrast to previously described cases of these tumours e.g. in mares and a bitch where a variety of clinical signs were described, for example: lameness, udder development, lactation and anorexia (Gardner et al 2005), progressive weight loss, diarrhoea and depression (Patrick et al 2003), anorexia (Sabocanec et al 1996Patrick et al 2003), and lameness (Gift et al 1992). Production of hormones in the neoplastic ovary may result in behavioural abnormalities and alterations in the oestrus cycle (Stabenfeldt et al 1979).…”
Section: Immunohistochemistrycontrasting
confidence: 49%
“…Gardner et al (2005) described the formation of lobules with central amphophilic material, too. This pattern of differentiation is frequently observed in early stages of bovine neoplasms, but is less common in other species and in large tumours (Kennedy and Miller 1993).…”
Section: Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…In mares, testosterone and inhibin assays have been utilised to enhance non-surgical ante-mortem diagnosis (McCue et al 2006). More recently AMH has been used as a highly sensitive and specific assay in both mares (Ball et al 2008(Ball et al , 2013 Lactogenesis in the absence of pregnancy has previously been reported in a ewe with GTCT (Gardner et al 2005). There are several reports of transient lactogenesis associated with GTCT in dairy cattle (Short et al 1963;Whitacre et al 1988;Palmer et al 2005), and in dairy cows transported by boat (Mansell et al 2014).…”
Section: Spontaneous Lactogenesis and Galactopoeisis In A Virgin Dairmentioning
confidence: 98%
“…Özellikle üç tümörün birlikte şekillendiği olgularda histopatolojik tanının zorlaş-ması nedeniyle, bu tümörlerin ayırıcı tanıları için immunohistokimyasal tekniklere ya da kan hormon-enzim seviyelerinin ölçülmesine gereksinim duyulmaktadır [10][11][12] . Sunulan çalışmada ise histopatolojik olarak kesin tanı için yeterli olan ve benzer granüloza hücre tümörü olgularının pek azında rastlandığı bildirilen tümöral hücrelerin rozet biçiminde dizilişi ile birlikte Call-Exner cisimciklerinin varlığı her iki olguda da bu tümörün tanımlanmasında yeterli olmuştur 3,7,13 . Granüloza hücre tümörlerinin hem insanlarda hem de hayvanlarda klinik muayenede abdominal şişkinliğe neden oldukları bildirilmektedir 7,14 .…”
Section: Tartişma Ve Sonuçunclassified